2019
DOI: 10.2478/cttr-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Extraction from Moist Snuff with Artificial Saliva of Benzo[a]pyrene and Other Polycyclic Aromatic Hydrocarbons

Abstract: SummaryThe present study evaluated in vitro extractability of various polycyclic aromatic hydrocarbons (PAHs) from moist snuff, when the extracting agent was water or artificial saliva. The extraction was performed on nine brands of moist snuff samples that are commercially available and were purchased from the market in January 2018. The moist snuff brands were selected to represent brands with different tobacco cut size descriptors and flavors. For the measurement of PAHs, two different analytical methods we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The R 2 value for the linear calibration was 0.9999. The method of HPLC analysis of BaP in moist snuff samples was very similar to the one previously reported (6) and no additional validation of the HPLC procedure has been made. The extraction was assumed to be 100%, previous work (6) indicating that no detectable BaP is found using a second extraction of the samples.…”
Section: Hplc Methods For Bap Analysis In Moist Snuff Samplesmentioning
confidence: 94%
See 3 more Smart Citations
“…The R 2 value for the linear calibration was 0.9999. The method of HPLC analysis of BaP in moist snuff samples was very similar to the one previously reported (6) and no additional validation of the HPLC procedure has been made. The extraction was assumed to be 100%, previous work (6) indicating that no detectable BaP is found using a second extraction of the samples.…”
Section: Hplc Methods For Bap Analysis In Moist Snuff Samplesmentioning
confidence: 94%
“…The method of HPLC analysis of BaP in moist snuff samples was very similar to the one previously reported (6) and no additional validation of the HPLC procedure has been made. The extraction was assumed to be 100%, previous work (6) indicating that no detectable BaP is found using a second extraction of the samples. However, the good reproducibility (relative standard deviation RSD% = 1.17%) of the measurement of the lowest calibration point (0.078 ng/mL) indicated that this value can be used as the LOQ value.…”
Section: Hplc Methods For Bap Analysis In Moist Snuff Samplesmentioning
confidence: 94%
See 2 more Smart Citations
“…Analyses of PAHs have been conducted in many areas, such as air [13], soil [14,15], sediment [16], sludgy [17], river and wastewater [18][19][20], smoke products [21,22], cosmetic products [23] and foods [24][25][26][27][28][29]. Recently, various analytical methods of PAHs for herbal medicines characterized by diverse matrices have been reported as follows.…”
Section: Introductionmentioning
confidence: 99%